(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The coastal forest area of Ambon Island plays an important ecological role in maintaining the stability of the coastal environment, preventing erosion, and supporting biodiversity. This area has unique ecological characteristics because it is directly influenced by the dynamics of the Banda Sea and the Seram Sea. The purpose of the study is to describe the factual condition of coastal forest vegetation in the tourist areas of the northern coastal region of Ambon Island, Maluku. The research was carried out in the northern coastal area of Ambon Island within the Central Maluku Regency, Maluku Province. The study used the species of forest vegetation growing in the northern coastal tourist areas of Ambon Island. Observation plots were determined purposively, data collection was conducted using the line quadrat method, and data analysis was carried out using vegetation analysis. The research results show that the vegetation growing and developing in the coastal areas of the northern part of Ambon Island consists of cultivated types and naturally growing vegetation. Cultivated species at the tree, pole, and stake or seedling stages are dominated by coconut (Cocos nucifera), canarium (Canarium indicum), nutmeg (Myristica fragrans), and sago (Metroxyloen spp.) with an average Importance Value Index (INP) of 45.4%. Meanwhile, natural vegetation species are dominated by Ketapang (Terminalia catappa), sea mango (Cerbera odollam), putat (Barringtonia asiatica), bintanggur (Calophyllum inophyllum), and pulai (Alstonia scholaris) with an average INP of around 39.1%. Specifically, vegetation at the seedling and ground cover stages is only dominated by naturally growing species such as alang-alang grass (Impereta cylindrica) and ferns (Nephrolepis exaltata) with an average INP of 48.1%.